The development of student’s soft skills in Tutorial Webinar (Tuweb) at Universitas Terbuka - A. Afriani; Paulina Pannen; Sri Dewi Nirmala; I. Isfarudi; Sendi Ramdhani (Inovasi Kurikulum, 2024)
This study aims to see the development of student soft skills in online learning at Universitas Terbuka (UT). The case study focused on postgraduate students at UT. The soft skills aspects are teamwork and communication in webinar tutorials (Tuweb) at the UT Postgraduate Program. The selected two aspects departed from the results of previous research, which observed the development of student soft skills in several aspects. Two aspects stand out in learning, namely teamwork and communication. The data collection instrument used was Focused Group Discussion (FGD). Data analysis uses content analysis. An important result of the research is that the two aspects of students' soft skills on Tuweb have developed as expected in online learning at UT. This result is an interesting reason for students to study at UT, considering that UT conducts online learning. Students' ability develops not only from the aspect of hard skills but also from the aspect of soft skills. The study's findings suggest that online learning can be an effective way for students to develop their soft skills.  AbstrakTujuan penelitian ini adalah untuk melihat perkembangan soft skill mahasiswa dalam pembelajaran daring di Universitas Terbuka (UT). Studi kasus berfokus pada mahasiswa pascasarjana di UT. Aspek soft skill yang dilihat adalah aspek kerjasama tim dan komunikasi dalam tutorial webinar (Tuweb) di Program Pascasarjana UT. Dua aspek yang dipilih berangkat dari hasil penelitian sebelumnya yang mengamati perkembangan soft skill mahasiswa pada beberapa aspek. Ada dua aspek yang menonjol dalam pembelajaran, yaitu kerjasama tim dan komunikasi. Instrumen pengumpulan data yang digunakan adalah Focused Group Discussion (FGD). Analisis data menggunakan content analysis. Hasil penting dari penelitian ini adalah pengembangan kedua aspek soft skill mahasiswa pada tuweb telah berkembang sesuai dengan yang diharapkan dalam pembelajaran daring di UT. Hasil tersebut menjadi alasan menarik mahasiswa untuk kuliah di UT, mengingat UT melaksanakan pembelajaran secara daring. Kemampuan peserta didik berkembang tidak hanya dari aspek hard skill saja tetapi juga dari aspek soft skill. Temuan penelitian menunjukkan bahwa pembelajaran online dapat menjadi cara yang efektif bagi siswa untuk mengembangkan soft skill mereka.Kata Kunci: Kerjasama; komunikasi; soft skill; tutorial online; tutorial webinar